Architecture of β-lactoglobulin coating modulates bioinspired alginate dialdehyde-gelatine/polydopamine scaffolds for subchondral bone regeneration - Ghorbani, Farnaz; Kim, Myong-Ho; Ghalandari, Behafarid; Zhang, Mingjing; Varma, Swastina Nath; Schöbel, Lisa; Liu, Chaozong; Boccaccini, Aldo R. (Acta Biomaterialia, 2024)
In this study, we developed polydopamine (PDA)-functionalized alginate dialdehyde-gelatine (ADA-GEL) scaffolds for subchondral bone regeneration. These polymeric scaffolds were then coated with β-Lactoglobulin (β-LG) at concentrations of 1 mg/ml and 2 mg/ml. Morphological analysis indicated a homogeneous coating of the β-LG layer on the surface of network-like scaffolds. The β-LG-coated scaffolds exhibited improved swelling capacity as a function of the β-LG concentration. Compared to ADA-GEL/PDA scaffolds, the β-LG-coated scaffolds demonstrated delayed degradation and enhanced biomineralization. Here, a lower concentration of β-LG showed long-lasting stability and superior biomimetic hydroxyapatite mineralization. According to the theoretical findings, the single-state, representing the low concentration of β-LG, exhibited a homogeneous distribution on the surface of the PDA, while the dimer-state (high concentration) displayed a high likelihood of uncontrolled interactions. β-LG-coated ADA-GEL/PDA scaffolds with a lower concentration of β-LG provided a biocompatible substrate that supported adhesion, proliferation, and alkaline phosphatase (ALP) secretion of sheep bone marrow mesenchymal stem cells, as well as increased expression of osteopontin (SPP1) and collagen type 1 (COL1A1) in human osteoblasts. These findings indicate the potential of protein-coated scaffolds for subchondral bone tissue regeneration. Statement of Significance: This study addresses a crucial aspect of osteochondral defect repair, emphasizing the pivotal role of subchondral bone regeneration. The development of polydopamine-functionalized alginate dialdehyde-gelatine (ADA-GEL) scaffolds, coated with β-Lactoglobulin (β-LG), represents a novel approach to potentially enhance subchondral bone repair. β-LG, a milk protein rich in essential amino acids and bioactive peptides, is investigated for its potential to promote subchondral bone regeneration. This research explores computationally and experimentally the influence of protein concentration on the ordered or irregular deposition, unravelling the interplay between coating structure, scaffold properties, and in-vitro performance. This work contributes to advancing ordered protein coating strategies for subchondral bone regeneration, providing a biocompatible solution with potential implications for supporting subsequent cartilage repair.
CRIS-Team Scopus Importer:2024-06-07
Keywords: 3D printing; Alginate dialdehyde-gelatine; Polydopamine; Tissue engineering; β-Lactoglobulin